Patient Experience in the Transition of Home Parenteral Nutrition Services Between Centers: Evaluation of a Transition Model. (September 2019) - Fletcher, Jane; Mumtaz, Saqib; Dera, Merceline; Cooper, Sheldon C
Background: In 2014, Dudley Group of Hospitals (DGH) underwent an organizational change that necessitated closure of their Home Parenteral Nutrition (HPN) service. University Hospitals Birmingham NHS Foundation Trust (UHBFT) transitioned 50 patients from DGH into their HPN service. The transition model included communication with patients, communication between centers (development of an HPN Patient Passport), and rapid follow-up on transition ensuring clinical care continued uninterrupted. Aim: Evaluate patient experience and their level of satisfaction with our HPN transition model. Method: A 19-point, mixed mode paper-based questionnaire was developed. Questionnaires were posted to 42 surviving patients still receiving HPN. Results: Response rate: 67%. Communication with patients: The transition was discussed with them, and they had appropriate contact details during the process—94%. Patients informed of patient transition meetings—97%. Attendance at meetings: DGH 89%, UHBFT 55%. Ongoing care at UHBFT: 86% very satisfied and 11% satisfied. Overall rating of the transition process: 79% very satisfied and 14% satisfied. Friends and Family Test: 82% "extremely likely" and 18% "likely" to recommend our services. Conclusion: The transition model used was successful, with the majority of patients "very satisfied" with how the transition was managed and their ongoing care. Effective communication with patients and between the 2 centers was the key to success. To our knowledge, this is the first report of transition of care for HPN patients. It is proposed that this model may be used by other centers to plan for future HPN service transitions where necessary.